2002
DOI: 10.1099/00221287-148-8-2383
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of spore cortex lytic enzymes and related proteins in Bacillus subtilis endospore germination

Abstract: The location and function of recognized cortex-lytic enzymes of Bacillus subtilis have been explored, and the involvement in germination of a number of related proteins tested. The SleB and CwlJ proteins are cortex-lytic enzymes, partially redundant in function, that are required together for effective cortex hydrolysis during B. subtilis spore germination. Spores were fractionated, and Western blotting of individual fractions suggests that the CwlJ protein is localized exclusively to the outer layers, or inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
187
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(200 citation statements)
references
References 32 publications
9
187
2
Order By: Relevance
“…The fluorescence of SleB 1-108 -GFP was localized around the spore's periphery, as about 75% of the dormant spores were surrounded by SleB 1-108 -GFP. Previous works have shown that SleB is translocated by a secretion signal peptide from the forespore compartment and located in the spore cortex of the dormant spore (Moriyama et al, 1999, Chirakkal et al, 2002. Thus, the peripheral location of SleB 1-108 -GFP suggests the deposition of the fusion protein in the spore cortex synthesized between the inner and the outer forespore membranes, which is consistent with that of wildtype SleB.…”
Section: Construction Of Cwldgere Mutantsupporting
confidence: 68%
See 1 more Smart Citation
“…The fluorescence of SleB 1-108 -GFP was localized around the spore's periphery, as about 75% of the dormant spores were surrounded by SleB 1-108 -GFP. Previous works have shown that SleB is translocated by a secretion signal peptide from the forespore compartment and located in the spore cortex of the dormant spore (Moriyama et al, 1999, Chirakkal et al, 2002. Thus, the peripheral location of SleB 1-108 -GFP suggests the deposition of the fusion protein in the spore cortex synthesized between the inner and the outer forespore membranes, which is consistent with that of wildtype SleB.…”
Section: Construction Of Cwldgere Mutantsupporting
confidence: 68%
“…From the results that SleB could not be detected immunochemically in the spore ingredients of ypeB mutant, Chirakkal et al concluded that YpeB might be required for the localization and/or stabilization of SleB (Chirakkal et al, 2002). However, our results suggested that SleB after translocation across the inner forespore membrane could be localized in the spore cortex mediated by the interaction between the peptidoglycan binding motif of SleB and the muramic δ-lactam in the spore cortex.…”
Section: Discussioncontrasting
confidence: 55%
“…The only muropeptides detected in supernatants untreated by muramidase were the anhydromuropeptides aG7a and aG7b ( Fig. 3E and F and Table 3), which were the only two products previously found to depend on in vivo SleB action (6,8,16,17). Exposure to SleB 125-253 led to an almost imperceptible decrease of insoluble cortex ( Fig.…”
Section: Structural Features Of Sleb and Its Overexpression And Purifmentioning
confidence: 99%
“…Following the activation of these receptors, spores release dipicolinic acid, calcium and amino acids (Moir, 2006;Setlow, 2003). Subsequently, the core of the spores becomes hydrated, and the spore cortex and sporespecific proteins are hydrolysed (Chirakkal et al, 2002;Sanchez-Salas et al, 1992;Setlow & Waites, 1976). Approximately 30 min after addition of germinants, the newly formed vegetative cells start to divide (Levinson & Hyatt, 1966;Setlow, 2003).…”
Section: Introductionmentioning
confidence: 99%